Intraoperative haemofiltration during on-pump cardiac surgery at Queen Alia Heart Institute - Awamlah, Ahmad A.; Hadidi, Abdallah A.; Shobaki, Wael A.; Qudah, Bashar A.; Badaren, Mutaz A.; Mohd, Ashraf F. (International Journal of Advances in Medicine, 2024)
Background: Objective of the study was to determine the frequency, indications and benefits of utilizing haemofiltration during cardiopulmonary bypass in adult cardiac surgical patients. Methods: This is a prospective observational analysis of data of adult cardiac surgical patients presented for on-pump cardiac surgery in the period between September 2023 and December 2023 at Queen Alia Heart Institute. Data was collected using Google Forms online and was subsequently recorded on Excel sheaths. Patients were divided into two groups: the haemofiltration group and the non-haemofiltration group. Both groups were compared according to perioperative laboratory and clinical variables. Statistical analysis of results using Microsoft excel followed data collection. Ethical committee approval was obtained. Results: Data from 130 adult cardiac surgical patients (105 males and 25 females) enrolled in this analysis showed that haemofiltration was used in 25 patients (19.2%). The most frequent indication for intraoperative haemofiltration was haemodilution in 14 patients (56%). Blood transfusion was needed in 17 (68%) of patients who had haemofiltration and in 35 (33.4%) of patients who did not need haemofiltration. Patients from the haemofiltration group were extubated 5 hours earlier than patients from the non-haemofiltration group, as the duration of mechanical ventilation in the ICU was 17.9 hours in the haemofiltration group versus 24.9 hours in the non-haemofiltration group. The average overall hospital stay was 3 days less in the haemofiltration group. Conclusions: Haemofiltration during cardiopulmonary bypass main indications were severe haemodilution, hyperkalaemia and preoperative renal impairment. The use of haemofiltration during CPB was associated with earlier tracheal extubation and shorter hospital stay.